In the family [videorecording (DVD)] - Wang, Patrick; Banes, Sebastian; St. John, Trevor; Kellermann, Susan (New Yorker Films, 2013)
Chip Hines, a precocious six-year-old, has only known life with his two dads, Cody and Joey. And a good life it is. When Cody suddenly dies in a car accident, Joey and Chip struggle to find their footing again. Just as they begin to, Cody's will reveals that he named his sister as Chip's guardian. The years of Joey's acceptance into the family unravel as Chip is taken away from him. Now Joey searches for a solution in order to find peace with the family and be closer to his son.